Institutional investors: do they have a role in the monitoring of corporate performance? - Nowak, Margaret; McCabe, Margaret (Curtin University of Technology, 2006)
In response to perceived anger of shareholders resulting from the combination of company failures, high termination payouts and CEO remuneration packages there has been growing media interest in assigning a role to institutional investors to participate as active monitors if corporate performance. This paper explores how institutional investors undertake the monitoring of corporate performance and governance processes and structures. Selected funds managers were interviewed about their approach to active institutional monitoring of invested companies.This article reports on the processes which funds managersindicated they adopted to monitor company performance and governance. It looks at managers' perceptions of the considerations which influenced the development of attitudes and polities about monitoring and the decision to undertake active monitoring and influencing activity. The processes and p rocedures through which exercise of real influence within invested companies is perceived to flow are discussed. The funds management industry is not homogeneous in its approach to active institutional monitoring and relations within vested companies. Thus future research to measure the impact on corporate performance of the presence of institutional investors on the share register may need to differentiate between categories of institutional investor.